Diversity and potential impact of insect pest on Parijoto plant (Medinilla sp.) cultivation in Colo, Kudus - Martitik, Dwiyani Anjar (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2025)
The Parijoto plant (Medinilla sp.) is an iconic and culturally significant species in Colo, Kudus, where many local farmers cultivate it. Based on preliminary interviews with farmers, several insect pests such as grasshopper and caterpillars have been reported to cause damage to the plants. The study aimed to identify potential impact of insect pests on Parijoto plant, asses their diversity and abundance, and analyze environmental factors that may influence their presence. The research was conducted in November 2022 using a survey method with three sampling periods. Insect collection was carried out using insect net and aspirators, while sample bottles were used for temporary storage before identification. Environmental factors, including light intensity, air humidity, soil humidity, and soil temperature, were also measured. A total of 11 potential insect pest species were identified, with the majority belonging to the orders Lepidoptera and Orthoptera. These findings provide valuable insight into the insect pests associated with Medinilla sp. in Colo, Kudus, which may help farmers develop better pest management strategies.